Penggunaan Big Data Dalam Mengungkap Kasus Kejahatan Judi Online di Polrestabes Medan - Tobing, Michael Yusuf; Markus Aruan, Miquel Joan; Pakpahan, Kartina (Pusat Kajian Hukum Perbankan Fakultas Hukum Universitas Jember, 2023)
One of the important benefits of Big Data and Computing Technology in criminal justice is that it is now easier to store and access records. Thanks to things like social media, people save more than usual. It is likely that the physical copies of the old photos are gone or destroyed, but many people have already posted them on Facebook. A criminal may post an incident, photo, or event on social media that can be traced to reveal the crime he committed and to punish or possibly release him. . To tackle gambling on the internet, Law no. 11 of 2008 concerning Electronic Information and Transactions. When dealing with